Keloidal Atypical Fibroxanthoma: Case and Review of the Literature - Emily Tongdee; Khasha Touloei; Paul K. Shitabata; Shahjahan Shareef; Eric L. Maranda (Karger Publishers, 2016)
Keloidal atypical fibroxanthoma (KAF) has recently been categorized as a variant of atypical fibroxanthoma. This paper will emphasize the importance of including KAF in both clinical and histological differential diagnosis of benign and malignant lesions which exhibit keloidal collagen and will also review the current literature on epidemiology, pathogenesis, histology, immunochemistry and treatments.